Eicosanoid Metabolomic Profile of Remdesivir Treatment in Rat Plasma by High-Performance Liquid Chromatography Mass Spectrometry - Du, Ping; Wang, Guo-yong; Zhao, Rui; An, Zhuo-ling; Liu, Li-hong (Frontiers in Pharmacology, 2021)
Remdesivir, a prodrug of nucleotide analogue, has displayed pharmacological activity against SARS-CoV-2. Recently, eicosanoids are widely involved in the regulating immunity and inflammation for COVID-19 patients. Rats were intravenously administered remdesivir at dose of 5 mg/kg, and series of blood samples were collected before and after treatment. Targeted metabolomics regarding eicosanoids profile were investigated and quantitated simultaneously using previous reported reliable HPLC-MS/MS method. Additionally, interplay relationship between metabolomics and pharmacokinetic parameters were performed using Pearson correlation analysis and PLS model. For the longitudinal metabolomics of remdesivir, metabolic profiles of the same rat were comparatively substantial at discrete sampling points. The metabolic fingerprints generated by individual discrepancy of rats were larger than metabolic disturbance caused by remdesivir. As for the transversal metabolomics, the prominent metabolic profiles variation was observed between the baseline and treatment status. Except for TXB2, the inflammatory and immunology related eicosanoids of Resolvin D2, 5-HEPE, 5-HETE, and DHA were significantly disturbed and reduced after single administration of remdesivir (p<0.05, p<0.001). Moreover, the metabolite of PGE2 correlated with GS-441524 (active metabolite of remdesivir) pharmacokinetic parameters of Cmax, AUC0-t, AUC0-infinity and CL significantly. Eicosanoids metabolic profiles of remdesivir at both longitudinal and transversal levels were firstly revealed using robust HPLC-MS/MS method. This initial observational eicosanoid metabolomics may lighten the therapy for fighting COVID-19, and further provide mechanistic insights of SARS-CoV-2 virus infection.